2018
DOI: 10.1093/aobpla/ply028
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chlorophyll and synthesis of flavonols during autumn senescence—the story told by individual leaves

Abstract: Chlorophylls are degraded and flavonoids synthesized during autumn senescence of deciduous trees. In the present study, chlorophyll and flavonol contents of individual leaves were monitored non-destructively throughout the autumn. Loss of chlorophyll and synthesis of flavonols were not gradual. Instead, each leaf maintained steady chlorophyll content until rapid chlorophyll degradation, accompanied by flavonol synthesis, was triggered. In ~1 week, the leaf turns yellow and falls. The pattern was similar in bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 62 publications
(74 reference statements)
4
57
0
1
Order By: Relevance
“…Until recently, leaf flavonol contents were generally considered not to increase during autumn, because of the presumed inefficiency of investing in leaves at the end of their life (reviewed by Wilkinson et al 2002). However, Mattila et al (2018) found that flavonols increase prior to and during autumn senescence in the tree species B. pendula and Sorbus aucuparia . Accordingly, we report an autumn increase in adaxial epidermal flavonol content in A. platanoides and Q. robur seedlings, as well as understory A. podagraria , and wintergreen F. vesca (Weeks 35-40).…”
Section: Discussionmentioning
confidence: 92%
“…Until recently, leaf flavonol contents were generally considered not to increase during autumn, because of the presumed inefficiency of investing in leaves at the end of their life (reviewed by Wilkinson et al 2002). However, Mattila et al (2018) found that flavonols increase prior to and during autumn senescence in the tree species B. pendula and Sorbus aucuparia . Accordingly, we report an autumn increase in adaxial epidermal flavonol content in A. platanoides and Q. robur seedlings, as well as understory A. podagraria , and wintergreen F. vesca (Weeks 35-40).…”
Section: Discussionmentioning
confidence: 92%
“…We found that OsSIRH2‐14 overexpression plants accumulated lower levels of H 2 O 2 compared with WT plants under the 200‐mM NaCl condition (Figure S5) but did not differ from WT under the 0‐mM NaCl condition. ROS compounds generated by salinity stress can lead to chlorophyll degradation and reduced photosynthetic activity (Mattila et al, ). Contents of both chlorophyll a (increase of approximately 2.3‐fold in #1 and 2.4‐fold in #2) and chlorophyll b (increase of approximately 2.6‐fold in #1 and threefold in #2) was significantly higher in transgenic plants compared with WT plants under 200‐mM NaCl treatment (Figure h,j).…”
Section: Resultsmentioning
confidence: 99%
“…Values represent means ± standard deviation, ns, nonsignificant, * P < .05, ** P < .01, and *** P < .001, two-tailed Student's t test [Colour figure can be viewed at wileyonlinelibrary.com] condition. ROS compounds generated by salinity stress can lead to chlorophyll degradation and reduced photosynthetic activity (Mattila et al, 2018). Contents of both chlorophyll a (increase of approximately 2.3-fold in #1 and 2.4-fold in #2) and chlorophyll b (increase of approximately 2.6-fold in #1 and threefold in #2) was significantly higher in transgenic plants compared with WT plants under 200-mM NaCl treatment (Figure 2h,j).…”
Section: Expression and Subcellular Localization Of Ossirh2-14 E3 Lmentioning
confidence: 96%
“…Also, the typical pattern of Chl and anthocyanins content changes during lifespan of leaves is well known, nevertheless, the dynamics of those changes is still unspecified. On the other hand, there is a lack of data describing the changes of flavonols content in leaves during the growing season, except the newest paper of Mattila et al (2018), in which authors described the changes of flavonols content in leaves of four tree species during senescence.…”
Section: Introductionmentioning
confidence: 99%